A review of financial-literacy education programs for children and adolescents. (April 2018) - Amagir, Aisa; Groot, Wim; Maassen van den Brink, Henriëtte; Wilschut, Arie
In this systematic literature review, we evaluate the effectiveness of financial-literacy education programs and interventions for children and adolescents. Furthermore, the key characteristics of the design of a successful financial-education curriculum are described. The evidence shows that school-based financial-education programs can improve children's and adolescents' financial knowledge and attitudes. Studies that assess the intention to practice good behavior and studies based on self-reported behavior also report positive effects. However, studies that assess the effects of financial education on children's and adolescent's actual financial behavior are scarce, and show hardly any effect. A promising method to teach financial literacy to children and adolescents in primary and secondary school is "experiential learning." In college, the focus should be on specific "life events" of students. The findings may be useful for designing an effective school-based financial education program.